The Clinical Presentation of Parkinson's Disease and the Dyadic Relationship between Patients and Carers : a Neuropsychological Approach. - Politynska, Barbara (Cambridge Scholars Publishing, 2013)
Providing care for someone with a neurodegenerative condition such as Parkinson's disease requires an integrated approach, taking into account the needs of the person with the disorder and family members most closely involved in their care. This is only possible with an understanding of the complex nature of Parkinson's disease, extending beyond the management of the motor disorder. It also requires an appreciation of the significant neuropsychological changes accompanying the disease, which ...